Early Outcomes Of Living Donor Liver Transplant Recipients In A University Teaching Hospital Of Nepal - Pradhan, Sumita; Maharjan, Narendra; Sharma, Deepak; Kandel, Bishnu; Hamal, Rabin; Bhattarai, Amit Sharma; Joshi, Pankaj; Shrestha, Pramesh Sunder; Paneru, Hem Raj; Acharya, Subhash P; Thapa, Ajit; Chataut, Dinesh; et al. (Journal of Society of Surgeons of Nepal, 2024)
Introduction: The burden of chronic liver disease (CLD) is on the rise and liver transplantation remains the best treatment modality for the end stage liver disease (ESLD). Tribhuvan University Teaching Hospital has started doing living donor liver transplantation (LDLT) and we aim to report our experience and early postoperative outcomes of the first 10 living donor liver transplants performed in our institute. Methods: This is a retrospective review and included all patients who were operated for LDLT from the year 2019 to 2023 for various indications. Demographic data, Model for End-Stage Liver Disease score, Child score, etiology of CLD, liver graft type, graft-to-recipient weight ratio, operative time, blood transfusion and complications were analysed. Results: From 2019 to 2023, in total, 10 patients underwent LDLT, including one paediatric transplant. The most common etiology was alcohol (50%) and right lobe was the preferred graft. The average operative time was 7.9 ± 2.56 hours. There were no re exploration or re transplantation. The mean duration of hospital stay was around 21.37 ± 6.43 days. All patients were followed for one to five years. Four recipients had Clavien Dindo Grade II and above complications, including bile leak and post-operative bleeding. One mortality occurred on 27th post-operative day due to covid infection. Conclusions: Living donor liver transplantation is a feasible option for patients with end stage liver disease and is safe to be performed in low volume centre with the help of expertise and good team work.